Antecedents of teachers’ emotions in the classroom: an intraindividual approach - Becker, Eva S.; Keller, Melanie M.; Goetz, Thomas; Frenzel, Anne C.; Taxer, Jamie L. (Frontiers in Psychology, 2015)
Using a preexisting, but as yet empirically untested theoretical model, the present study investigated antecedents of teachers’ emotions in the classroom. More specifically, the relationships between students’ motivation and discipline and teachers’ enjoyment and anger were explored, as well as if these relationships are mediated by teachers’ subjective appraisals (goal conduciveness and coping potential). The study employed an intraindividual approach by collecting data through a diary. The sample consisted of 39 teachers who each participated with one of their 9th or 10th grade mathematics classes (N = 758 students). Both teachers and students filled out diaries for two to three weeks pertaining to 8.10 lessons on average (N = 316 lessons). Multilevel structural equation modeling revealed that students’ motivation and discipline explained 24% of variance in teachers’ enjoyment and 26% of variance in teachers’ anger. In line with theoretical assumptions, after introducing teachers’ subjective appraisals as a mediating mechanism into the model, the explained variance systematically increased to 65% and 61%, for teachers’ enjoyment and anger respectively. The effects of students’ motivation and discipline level on teachers’ emotions were partially mediated by teachers’ appraisals of goal conduciveness and coping potential. The findings imply that since teachers’ emotions depend to a large extent on subjective evaluations of a situation, teachers should be able to directly modify their emotional experiences during a lesson through cognitive reappraisals.